The Effect of Cooperative Learning Model with Student Team Achievemen Division (STAD) Type on Motivation and Learning Outcomes - Rosyadi, Imron; Purwanto, Burhan Eko; Mulyono, Tri (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of the Student Teams-Achievement Divisions (STAD) cooperative learning model on students' motivation and learning outcomes in the topic of function limits in class XI IPS at SMA Negeri 1 Pangkah. The method used is quantitative with a true experimental design, involving 72 students from class XI IPS 4 as the experimental group and XI IPS 5 as the control group. Data were collected through pre-tests and post-tests to evaluate the differences in learning outcomes and motivation before and after the implementation of the STAD model. The results indicate a significant increase in students' motivation and learning outcomes following the application of the STAD model. Meaningful learning, effective discussion coordination, and motivation to collaborate are key factors for the success of this model. Teachers are also expected to present engaging lessons to enhance student enthusiasm and involvement in the learning process.